PENGARUH PELATIHAN, TUNJANGAN KINERJA DAN PENERAPAN MANAJEMEN RESIKO TERHADAP POTENSI KECURANGAN PEGAWAI - Andi Nadirah; Hendra Setiawan (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
Fraudulent behavior carried out by Civil Servants does not only focus on corruption, Training of employees has an important role in improving performance so it is very important to be applied in an agency, Performance allowances or remuneration can provide additional income to each employee, so that employees are more concentrated in working . The remuneration system for each employee is part of the bureaucratic reform implemented by the government. Risk management is initiated because of the awareness of management realizing that risk must exist within an agency. The implementation of good risk management must ensure that an organization is able to provide appropriate handling of risks that will exist and affect the system of an organization. Information on risk management is useful for stakeholders, this information is used to conduct risk analysis so that the expected objectives can be met.